Effect of Chemical Composition on Average γ/α' Orientation Relationship in Carbon and Low Alloy Steels. (2015) - Pham, A.H.; Ohba, T.; Morito, S.; Hayashi, T.
Abstract: In the present study, the average γ/ α′ orientation relationship (OR) was quantified for three series of carbon and low alloy steels. The OR of given steel can be calculated from electron backscatter diffraction (EBSD) data of martensite inherited from one prior-austenite grain. This OR is virtually independent on both prior-austenite grain size and quenching rate. The OR is characterized by small deviation θ 1 between (111)γ & (011)α′ and θ 2 between . Dissolution of C as interstitial impurity causes decrease of θ 1 and non-uniform variation of θ 2 . Addition of Mn or Ni as substitutional impurities up to 3 mass% mainly causes increase of θ 1 . For the same amount of dissolution, Mn shows slightly stronger effect on θ 1 than Ni.